Strategi ‘Jari Manis’: Pemertahanan Tenun Ikat di Tengah Krisis Regenerasi Penenun di Desa Julah Bali Utara - I Gusti Agung Ngurah Agung Yudha Pramiswara; I Putu Mardika (Jurnal Kajian Bali (Journal of Bali Studies), 2023)
The Julah Village in North Bali is known for its traditional ikat cloth crafts. However, the number of weavers is currently declining, which is due in part to the regeneration problem. This research examines factors contributing to the shortage of ikat weaving, and it comes to the conclusion that the absence of regeneration in the inheritance process is the primary cause. Following closely behind is the need for a variety of processes in weaving production, and finally, a prolonged and expensive process for producing ikat. There are a number of initiatives that can be performed to help encourage younger generations to be interested in weaving, such as socialization, enculturation, and collaboration using tradition-based regulations. The lack of Julah Traditional Ikat weaving signifies that it's impracticable to perform religious rituals, which is the implication of scarcity in the religious system. This article offers Jari Manis strategy (Julah Mandiri, Manjemen, Investasi or Julah Independent, Management, and Investment) to stimulate weaving production, including for the local younger generation.